2013
DOI: 10.1038/hr.2013.7
|View full text |Cite
|
Sign up to set email alerts
|

Association between hypertension status and the screening test for frailty in elderly community-dwelling Japanese

Abstract: To clarify the possible association of frailty with hypertension prevalence, treatment and blood pressure (BP) control in the elderly, we conducted a screening survey of 1091 elderly community-dwelling subjects aged ≥65 years, using data from public health check-ups and frailty was determined by a 25-item questionnaire, the Basic Checklist for Frailty (BCF). The significance of differences in the association of BCF categories or BCF items with each hypertension status was analyzed using multiple logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 32 publications
1
31
0
Order By: Relevance
“…24 There is no consensus regarding the division of the KCL domains; some researchers considered the first domain of the KCL as the first five questions (naming it "instrumental activities of daily living -IADL"), 12,17,20,23 whereas others considered it as the sixth to tenth questions, for example. Although the majority of studies divided the domains as aforementioned, exceptions were observed.…”
Section: Kcl Terminologymentioning
confidence: 99%
See 3 more Smart Citations
“…24 There is no consensus regarding the division of the KCL domains; some researchers considered the first domain of the KCL as the first five questions (naming it "instrumental activities of daily living -IADL"), 12,17,20,23 whereas others considered it as the sixth to tenth questions, for example. Although the majority of studies divided the domains as aforementioned, exceptions were observed.…”
Section: Kcl Terminologymentioning
confidence: 99%
“…1,10 Furthermore, the next domain includes questions six to ten and has been named "physical strength domain," 11,15,20 "walking status domain," 14,23 "physical domain," 17 "motor function domain,"…”
Section: Kcl Terminologymentioning
confidence: 99%
See 2 more Smart Citations
“…72 In a study by Koizumi et al, 73 frailty in hypertensive patients was associated with limited physical activity, lower body weight, difficulties in ingesting solid foods and performing daily activities, and limitations in performing complex activities of daily living, correlated with the prevalence, treatment and control of hypertension. 73 In another study, Talegawkar et al 74 investigated associations between frailty and adherence to the Mediterranean diet, and found that non-frail patients were more compliant with dietary recommendations than frail patients. 74 Contrary to the above, Chao et al report better adherence in frail patients, though not in the hypertensive population.…”
Section: Adherence To Treatment In the Elderly Populationmentioning
confidence: 99%